Kur’an ve Sünnet Perspektifinden Dînen Kıyemen Mefhumu ve Kapsamı - Çelik, Nizamettin (Adıyaman Üniversitesi, 2021)
Kur’an’da dinen kıyemen vurgusu, İslam’ın delil ve hüccetle desteklenen, dengeli, ilkeli, uyumlu ve dosdoğru bir din olduğunu göstermektedir. Dünya ve ahiret saadetini sunan İslam, hem özünde ilkeli bir dindir hem de namaz, zekât gibi yaşamsal alanda ilkeler üzerine bina edilmiştir. Bu ilkelerin de kendi için rükün ve şartları vardır. Devamlılık ve düzen bu ilkelerin ayrılmaz parçasıdır. İslam, ilkeli ve ilke temelli bir din olduğundan onda içtimai, iktisadi, siyasi, hukuki, kültürel ve bireysel alanların hiçbirinde keyfî hareket etme yoktur. Yaşadığımız çağda insan, yeni ilimlerde ve teknolojide çok yönlü ilerleme kaydetmiştir. Ancak tüm bu ilerlemelerin yanında ilkeler ve değerler boyutunda da gerilemiştir. İnsanoğlunun ürettiği nükleer ve kimyasal silahlar yerküreyi bir anda yaşanmaz hâle getirebilmektedir. Bu ilkesiz ve ölçüsüz ilerleyiş karşısında insan hayatı, değersiz konuma düşebilmektedir. Ma’mur ve yaşanır bir dünya ancak ilkeli yaşamla sağlanabilir.

The emphasis on “kıyemen religion” (a religion that is straightforward, stable, continuous, always preserving its existence, reality, and effectiveness) in the Qur’an shows that Islam is a balanced, principled, harmonious and straightforward religion supported by evidence and hujjat (paper, witness). Offering the happiness of the world and the hereafter, Islam is both a principled religion and built on vital principles such as salaah (prayer) and zakah (obligatory alms). These principles also have conditions and elements for them. Continuity and order are an integral part of these principles. Since Islam is a principled and principle-based religion, there is no arbitrary action in any of the social, economic, political, legal, cultural, and individual fields. In the age we live in, human beings have made multifaceted progress in new sciences and technology. However, in addition to all these advances, it also declined in terms of principles and values. Nuclear and chemical weapons produced by human beings can instantly make the earth uninhabitable. In the face of this unprincipled and disproportionate progress, human life may fall into a worthless position. A prosperous and livable world can only be achieved through principled life.
Kur’an ve Sünnet Perspektifinden Dînen Kıyemen Mefhumu ve Kapsamı
Keywords: Religion; Society and Culture Studies; Din; Toplum ve Kültür Araştırmaları